Epistemological fundaments of science and technology policies in Latin America - Mejía Navarrete, Julio (2021)
This essay on the epistemological fundaments of science and technology policies, concerning the field of social sciences, analyses the basis of the strategic order leading the cognitive production and circulation in Latin America. Precisely, the expository structure of the article turns around its main epistemological categories: the Cartesian principle of the two cultures, the hegemonic cognitive Eurocentrism, the appropriation of knowledge from the periphery and the extinction of the author-function in globalization times.